2020
DOI: 10.3390/app10175987
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Evaluation of Hand Sanitiser Production Using Oil Palm Empty Fruit Bunch-Based Bioethanol by Simultaneous Saccharification and Fermentation (SSF) Process

Abstract: Oil palm empty fruit bunch (OPEFB) is a potential raw material abundantly available for bioethanol production. However, the second-generation bioethanol is still not yet economically feasible. The COVID-19 pandemic increases the demand for ethanol as the primary ingredient of hand sanitisers. This study evaluates the techno-economic feasibility of hand sanitiser production using OPEFB-based bioethanol. OPEFB was alkaline-pretreated, and simultaneous saccharification and fermentation (SSF) was then performed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Akan tetapi, TKKS dapat digunakan sebagai bahan baku fermentasi untuk menghasilkan berbagai produk bernilai dikarenakan jumlahnya sangat melimpah dan murah [6]. Salah satu bioproduk yang paling umum yang dapat dikonversi dari TKKS adalah bioetanol [7]. 156 TKKS merupakan biomassa lignoselulosa yang terdiri dari fraksi selulosa, hemiselulosa dan lignin.…”
Section: Pendahuluanunclassified
“…Akan tetapi, TKKS dapat digunakan sebagai bahan baku fermentasi untuk menghasilkan berbagai produk bernilai dikarenakan jumlahnya sangat melimpah dan murah [6]. Salah satu bioproduk yang paling umum yang dapat dikonversi dari TKKS adalah bioetanol [7]. 156 TKKS merupakan biomassa lignoselulosa yang terdiri dari fraksi selulosa, hemiselulosa dan lignin.…”
Section: Pendahuluanunclassified
“…Many studies reported the potential use of OPEFB as the feedstock of bioethanol production due to its high cellulose content [ 7 , 23 , 24 , 25 ]. Saccharomyces cerevisiae is the most commonly employed yeast for commercial ethanol production, although various yeasts, bacteria, and other microorganisms can produce ethanol [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Saccharification is first done to hydrolyze cellulose into glucose through cellulase enzyme, followed by fermentation, where glucose is converted into ethanol through yeast [3]. Simultaneous Saccharification and Fermentation (SSF) is a method to produce bioethanol from lignocellulosic biomass where both processes occur in a single reaction at one time [4]. Bamboo is one of the most abundant natural resources in many countries, particularly those located in Asia.…”
Section: Introductionmentioning
confidence: 99%